A primitive hadrosaurid from southeastern North America and the origin and early evolution of 'duck-billed' dinosaurs. Issue 2 (3rd March 2016) - Prieto-Marquez, Albert; Erickson, Gregory M.; Ebersole, Jun A.
ABSTRACT: Eotrachodon orientalis gen. et sp. nov. (latest Santonian of Alabama, southeastern U.S.A.) is one of the oldest and most basal hadrosaurid dinosaurs and the only hadrosaurid from Appalachia (present day eastern North America) with a preserved skull. This taxon possesses a relatively derived narial structure that was until now regarded as synapomorphic for saurolophine (solid-crested or crestless) hadrosaurids. Maximum parsimony analysis places E. orientalis as the sister taxon to Saurolophidae (Saurolophinae + Lambeosaurinae). Character optimization on the phylogeny indicates that the saurolophine-like circumnarial structure evolved by the Santonian following the split between saurolophines and lambeosaurines but prior to the major hadrosaurid radiation. Statistical dispersal-vicariance analysis posits an Appalachian ancestral area for Hadrosauridae and subsequent dispersal of their ancestors into Laramidia (present-day western North America) during the Cenomanian. http://zoobank.org/urn:lsid:zoobank.org:pub:3AD914D2-A3A5-45FD-8C94-5EE80461FEBC SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Prieto-Márquez, A., G. M. Erickson, and J. A. Ebersole. 2016. A primitive hadrosaurid from southeastern North America and the origin and early evolution of 'duck-billed' dinosaurs. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2015.1054495